Targeting Endothelial Dysfunction in Eight Extreme-Critically Ill Patients with COVID-19 Using the Anti-Adrenomedullin Antibody Adrecizumab (HAM8101) - Mahir Karakas; Dominik Jarczak; Martin Becker; Kevin Roedl; Marylyn M. Addo; Frauke Hein; Andreas Bergmann; Jens Zimmermann; Tim-Philipp Simon; Gernot Marx; Marc Lütgehetmann; Axel Nierhaus; et al. (Biomolecules, 2020)
Recently, the stabilization of the endothelium has been explicitly identified as a therapeutic goal in coronavirus disease 2019 (COVID-19). Adrecizumab (HAM8101) is a first-in-class humanized monoclonal anti-Adrenomedullin (anti-ADM) antibody, targeting the sepsis- and inflammation-based vascular and capillary leakage. Within a “treatment on a named-patient basis” approach, Adrecizumab was administered to eight extreme-critically ill COVID-19 patients with acute respiratory distress syndrome (ARDS). The patients received a single dose of Adrecizumab, which was administered between 1 and 3 days after the initiation of mechanical ventilation. The SOFA (median 12.5) and SAPS-II (median 39) scores clearly documented the population at highest risk. Moreover, six of the patients suffered from acute renal failure, of whom five needed renal replacement therapy. The length of follow-up ranged between 13 and 27 days. Following the Adrecizumab administration, one patient in the low-dose group died at day 4 due to fulminant pulmonary embolism, while four were in stable condition, and three were discharged from the intensive care unit (ICU). Within 12 days, the SOFA score, as well as the disease severity score (range 0–16, mirroring critical resources in the ICU, with higher scores indicating more severe illness), decreased in five out of the seven surviving patients (in all high-dose patients). The PaO2/FiO2 increased within 12 days, while the inflammatory parameters C-reactive protein, procalcitonin, and interleukin-6 decreased. Importantly, the mortality was lower than expected and calculated by the SOFA score. In conclusion, in this preliminary uncontrolled case series of eight shock patients with life-threatening COVID-19 and ARDS, the administration of Adrecizumab was followed by a favorable outcome. Although the non-controlled design and the small sample size preclude any definitive statement about the potential efficacy of Adrecizumab in critically ill COVID-19 patients, the results of this case series are encouraging.